Strategi Pengembangan Budidaya Laut Di Kabupaten Raja Ampat Mariculture Development Strategy in Raja Ampat Regen - Subandiyono Subandiyono; Richard Latuny; Eddy Supriyono; Sri listyarini; Nur Hasanah (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2022)
The purpose of this study was to analyze the internal and external environment as well as the right strategy for Raja Ampat Regency in the process of developing fisheries in Capture Fish cultivation. The research method used is the questionnaire method and in-depth interviews using FGD to obtain the SWOT variable (Strengths, Weaknesses, Opportunisities , Threats). The results showed that the strength of the Raja Ampat archipelago consisted of strategic geographical position, high potential of aquaculture, available cultivation land, and available labor. While the weaknesses consist of limited seed log size, fish mortality caused by disease, low water quality management, limited trash feed, limited capital, low skills, knowledge of cultivation technology, and limited access to markets. Opportunities for grouper farmers in Raja Ampat district consist of high fish prices, wide open market demand, increased income of coastal communities, absorption of labor, regional autonomy, RTRW / RTWRPL / Kab. Zoning Plans. Raja Ampat, National Policy in fisheries development. While threats consist of climate change / season, lack of market guarantee, determination of quality standards for aquaculture products, low capital support, safety, environmental pollution, and lack of enforcement of RTRW regulations for fisheries cultivation development. In this case, the right strategy in this case is maximizing strength in taking advantage of opportunities, taking advantage of opportunities to suppress weaknesses, maximizing strength to avoid threats, and suppressing weaknesses and avoiding threats.